2011
DOI: 10.1021/nn200267c
|View full text |Cite
|
Sign up to set email alerts
|

How the Surface Nanostructure of Polyethylene Affects Protein Assembly and Orientation

Abstract: Protein adsorption plays a key role in the biological response to implants. We report how nanoscale topography, chemistry, crystallinity, and molecular chain anisotropy of ultrahigh molecular weight polyethylene (UHMWPE) surfaces affect the protein assembly and induce lateral orientational order. We applied ultraflat, melt drawn UHMWPE films to show that highly oriented nanocrystalline lamellae influence the conformation and aggregation into network structures of human plasma fibrinogen by atomic force microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(89 citation statements)
references
References 49 publications
5
82
2
Order By: Relevance
“…In fact, a recent study on ultrahigh molecular weight polyethylene surfaces suggests that nanotopography, chemistry, crystallinity, and molecular chain anisotropy could affect protein and assembly at the same time [79]. It is possible, as demonstrated by the study, that nanotopography loses its effectiveness on mediating protein adsorption when surface chemistry and hydrophobicity are changed.…”
Section: Selective Protein Adsorptionmentioning
confidence: 87%
“…In fact, a recent study on ultrahigh molecular weight polyethylene surfaces suggests that nanotopography, chemistry, crystallinity, and molecular chain anisotropy could affect protein and assembly at the same time [79]. It is possible, as demonstrated by the study, that nanotopography loses its effectiveness on mediating protein adsorption when surface chemistry and hydrophobicity are changed.…”
Section: Selective Protein Adsorptionmentioning
confidence: 87%
“…[91] Diverse grades of PE are widely applied or are in development as biomaterials for ligament replacement, cochlear implants, composites for skull implants, or syringes, tubes, infusion bags, and packing. [72,92] Under standard conditions, melt-drawn UHMWPE forms staggered and stacked lamellar crystals oriented perpendicular to the drawing direction, [93] while iPB-1 forms long extended needle-like crystals [11] ( Figure 3b). The needle crystals align parallel to the drawing direction of the polymer film and their lengths range from a few nanometers to some micrometers, while their diameter is found to be 25-35 nm.…”
Section: Semicrystalline Polymersmentioning
confidence: 99%
“…Keller et al showed that ordered crystalline lamellae of UHWMPE with dimensions similar to the size of the fibrinogen molecules favor preferential alignment of single proteins with their long axis parallel to the lamellae major axis. [93] With nearly a monolayer coverage, fibrinogen molecules assembled into an ordered, densely packed film with Adv. Healthcare Mater.…”
Section: Protein Adsorption Behavior On Nanostructured Semicrystallinmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface-bonded HPF has a length of 46-49 nm and a height about 0.3-2.5 nm depending on the protein conformation on different substrates and under different environmental conditions [7,[10][11][12][13]. Former studies mostly investigated the adsorption of HPF and a variety of other proteins [14,15] on flat substrates such as commercially pure Ti with a natural TiO 2 layer on top [13], TiO 2 [7], graphite [10,11,16], mica [10,12,13], ultra-high molecular weight polyethylene [17], Si [18] or SiO 2 [19]. In most cases, these investigations concentrated on the adsorption of single proteins in air and/or under aqueous conditions.…”
Section: Introductionmentioning
confidence: 99%